Frequency switching multiwavelength Brillouin Raman fibre laser based on feedback power adjustment technique - Ahmad, Harith; Al-Alimi, Abdulmoghni Wazae; Abdul Kadir@Jaafar, Muhammad Zamzuri; Bayang, Leonard; Ismail, Mohammad Faizal; Thambiratnam, Kavintheran (Taylor and Francis Ltd., 2020)
A simple switchable multiwavelength Brillouin–Raman fibre laser (BRFL) was demonstrated. The laser was arranged in a half-open cavity configuration including a physical mirror device with an adjustable reflectivity at one side of the laser cavity. The impact of the feedback power adjustment on frequency switching was carried out by comparing the peak power difference between odd- and even-order Stokes lines. Up to 468 flat-amplitude lines with a 10 GHz frequency spacing and average optical signal to noise ratio (OSNR) of 33 dB were observed with mirror reflectivity values of ∼15% up to 60% at a 1534nm Brillouin pump power of 7 dBm and 0.9W Raman pump power of 0.9 W. Under the same pumping conditions, setting the mirror reflectivity at its OFF state (where reflectivity is nearly 0%) allows for up to 242 lines with 20 GHz spacing to be realized, with ONSR values of ∼35 dB.